Genital Hiatus Size as a Predictor of Progression of Pelvic Organ Prolapse. Issue 6 (June 2021) - Woll, Abbigail; Mbaye, Marieme; Edenfield, Autumn; Swift, Steven
Abstract : Objective: This study aimed to determine if genital hiatus (GH) size is a predictor of worsening pelvic organ prolapse and a preference for a therapeutic intervention in women with pelvic organ prolapse who opt for expectant management over therapeutic intervention at their initial encounter. Methods: This was a retrospective cohort study analyzing the GH size of women who opted for expectant management in the initial treatment of pelvic organ prolapse at one academic institution from 2002 to 2015. Participants were divided into 2 groups: (1) large GH was defined as ≥4 cm and (2) normal GH was defined as <4 cm. The primary outcome was women opting for therapeutic intervention for their prolapse at a later visit, defined as pessary insertion or surgical intervention. Secondary measures evaluated GH as a predictor of worsening anatomy or symptoms. Results: One hundred eleven participants were enrolled. Fifty-two women had a large GH, and 59 women had a normal GH. Median length of follow-up was 24 months (range, 6–110 months). Of the 52 with a large GH, 22 (42%) opted for intervention; of the 59 women with a normal GH, 16 (27%) opted for intervention. There was no statistically significant difference between groups in the number who eventually chose intervention ( P = 0.09). There was no difference in secondary outcomes between groups with respect to worsening bother, worsening pelvic organ prolapse quantification stage, or an increase in the prolapse leading edge of ≥2 cm. Conclusions: Women with a large GH, when compared with those with a normal GH, were not more likely to choose intervention over continued observation. Abstract : A large genital hiatus is not a predictor of worsening pelvic organ prolapse in untreated pelvic organ prolapse.